Predicting study success of international students at English-speaking universities. - Michael Daller (Bloomsbury Applied Linguistics Review, 2013)
More and more students study outside their own countries and by 2020 a rise to 7 million international students is predicted world-wide. The present study investigates the level of language proficiency that is necessary for international students to study successfully at universities in English-speaking countries and how this proficiency can be measured. Standardized tests such as the International English Language Test System (IELTS) or the Test of English as a Foreign Language (TOEFL) are carefully developed and constantly scrutinized by the research community, and they provide a valid cut-off point for entry to university, but they do not seem to be good predictors of study success on their own. This is mainly due to the fact that most students who enter universities with these tests have similar scores which leave researchers with a truncated sample where correlations between these test scores and study success, e.g. marks obtained after one year, are necessarily low. The present study investigates alternative measures of language proficiency that can predict the study success of international students. In a longitudinal study with 74 international students a battery of language tests was used at the beginning of the academic year to predict the average marks that the students obtained at the end of the academic year. Several multiple regressions show that between 33% and 96% of the marks can be predicted with tests based mainly on vocabulary knowledge. The findings of the present study have implications for decisions on admission criteria and for language support provision in addition to subject specific learning. There may be many factors other than language proficiency that influence study success of international students such as cultural factors, motivation and familiarity with the subject area. However, our findings indicate that language proficiency and especially vocabulary knowledge is the key factor that explains in some cases almost entirely the final marks that the students achieve.